2013
DOI: 10.4300/jgme-d-12-00085.1
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Competency Training Requirements in Graduate Medical Education

Abstract: Background Cultural competency is an important skill that prepares physicians to care for patients from diverse backgrounds. Objective We reviewed Accreditation Council for Graduate Medical Education (ACGME) program requirements and relevant documents from the ACGME website to evaluate competency requirements across specialties. Methods The program requiremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 14 publications
1
24
0
Order By: Relevance
“…Although prioritized by the ACGME, cultural competency requirements vary greatly across specialties, with no defined competency requirements among plastic surgery and urology specialties, especially related to transgender patient care. 13 Within the milestones for plastic surgery and urology, there is a similar absence of focused content on gender-confirming procedures, which highlights the importance of expanding resident education in transgender populations. Previous studies have demonstrated a positive correlation between exposure to LGBT patients and more favorable attitudes toward treating this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Although prioritized by the ACGME, cultural competency requirements vary greatly across specialties, with no defined competency requirements among plastic surgery and urology specialties, especially related to transgender patient care. 13 Within the milestones for plastic surgery and urology, there is a similar absence of focused content on gender-confirming procedures, which highlights the importance of expanding resident education in transgender populations. Previous studies have demonstrated a positive correlation between exposure to LGBT patients and more favorable attitudes toward treating this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Communication skills training and assessment are required in medical education and for licensure, but education and training in other aspects of the compassion process described above are not. Some aspects of this process may be taught in existing curricula but expectations and training vary considerably across learning stages and disciplines . Compassion may be included as a topic in palliative care curricula.…”
Section: A Framework To Inform Education and Skills Training To Buildmentioning
confidence: 99%
“…27 Cultural competency education, as a component of core curriculums, is an expectation in nursing schools that offer bachelor's degrees (BSN). 25 Thus, NPs receive this education early in their career training as health care providers, and they may continue to draw from it in their active 29 However, since there are no standard curricula, the degree to which residency programs are incorporating these mandates remains uncertain. 26,28,30 Furthermore, results are consistent with those of prior studies that found physicians to be generally wary of using race in clinical decision-making.…”
Section: Discussionmentioning
confidence: 99%